CDKN1B mutation and copy number variation are associated with tumor aggressiveness in luminal breast cancer. Issue 2 (4th December 2020) - Viotto, Davide; Russo, Francesca; Anania, Ilaria; Segatto, Ilenia; Rampioni Vinciguerra, Gian Luca; Dall'Acqua, Alessandra; Bomben, Riccardo; Perin, Tiziana; Cusan, Martina; Schiappacassi, Monica; Gerratana, Lorenzo; D'Andrea, Sara; et al.
Abstract: The CDKN1B gene, encoding for the CDK inhibitor p27 kip1, is mutated in defined human cancer subtypes, including breast, prostate carcinomas and small intestine neuroendocrine tumors. Lessons learned from small intestine neuroendocrine tumors suggest that CDKN1B mutations could be subclonal, raising the question of whether a deeper sequencing approach could lead to the identification of higher numbers of patients with mutations. Here, we addressed this question and analyzed human cancer biopsies from breast ( n  = 396), ovarian ( n  = 110) and head and neck squamous carcinoma ( n  = 202) patients, using an ultra‐deep sequencing approach. Notwithstanding this effort, the mutation rate of CDKN1B remained substantially aligned with values from the literature, showing that essentially only hormone receptor‐positive breast cancer displayed CDKN1B mutations in a relevant number of cases (3%). However, the analysis of copy number variation showed that another fraction of luminal breast cancer displayed loss (8%) or gain (6%) of the CDKN1B gene, further reinforcing the idea that the function of p27 kip1 is important in this type of tumor. Intriguingly, an enrichment for CDKN1B alterations was found in samples from premenopausal luminal breast cancer patients ( n  = 227, 4%) and in circulating cell‐free DNA from metastatic luminal breast cancer patients ( n  = 59, 8.5%), suggesting that CDKN1B alterations could correlate with tumor aggressiveness and/or occur later during disease progression. Notably, many of the identified somatic mutations resulted in p27 kip1 protein truncation, leading to loss of most of the protein or of its C‐terminal domain. Using a gene‐editing approach in a luminal breast cancer cell line, MCF‐7, we observed that the expression of p27 kip1 truncating mutants that lose the C‐terminal domains failed to rescue most of the phenotypes induced by CDKN1B gene knockout, indicating that the functions retained by the C‐terminal portion are critical for its role as an oncosuppressor, at least in luminal breast cancer. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.